Is prostate-specific antigen density superior than prostate-specific antigen kinetics and prostate volume in predicting clinically insignificant prostate cancer? - Avcı, Sinan; Ekici, Özgür; Çağlayan, Volkan; Erdoğan, Abdullah; Önen, Efe; Akgün, Uğur; Özcan, Rıdvan; Öner, Sedat (The European Research Journal, 2025)
Objectives: In this study, we aimed to evaluate the parameters that could predict clinically insignificant prostate cancer (ciPCa) in men who underwent transrectal ultrasound (TRUS)-guided prostate biopsy. Methods: Data of patients who underwent transrectal prostate biopsy between January 2015 and November 2019 were examined retrospectively. Free/total PSA ratio (fPSA%), serum total and free prostate-specific antigen (PSA) levels, prostate volumes (PV) measured by ultrasonography, and PSA density (PSAD) values of the patients before biopsy were recorded. ciPCa patients were defined as patients with Gleason scores ≤6 and clinical stage ≤T2a (Group 1). The remaining patients (Gleason score >6 and clinical stage >T2a) were included in Group 2 (clinical significant prostate cancer (csPCa). The parameters examined before biopsy were compared between groups. Results: After performing the exclusion criteria, the study counts in 168 patients with the current data of total/free PSA levels, age, PV calculated by TRUS, rectal examination findings, and pathology reports. Group 1 consisted of 115 patients and Group 2 consisted of 53 patients. In the univariate analysis, PV, total PSA and PSAD were found significantly different between groups, while age, free PSA, and fPSA% showed no significant difference between the two groups. According to the results of the multivariate analysis, the independent predictor of ciPCa was determined to be PSAD while total PSA and PV were not independent predictors. Conclusion: PSAD was found to be superior to other PSA kinetics in predicting ciPCa.